1999
DOI: 10.1152/jappl.1999.87.2.471
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoplasmic reticulum Ca2+release and muscle fatigue

Abstract: Efforts to examine the relevant mechanisms involved in skeletal muscle fatigue are focusing on Ca2+ handling within the active muscle cell. It has been demonstrated time and again that reductions in sarcoplasmic reticulum (SR) Ca2+release resulting from increased or intense muscle contraction will compromise tension development. This review seeks to accomplish two related goals: 1) to provide an up-to-date molecular understanding of the Ca2+-release process, with considerable attention devoted to the SR Ca2+ c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
1
7

Year Published

2002
2002
2010
2010

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(101 citation statements)
references
References 144 publications
(169 reference statements)
6
87
1
7
Order By: Relevance
“…[27][28][29] It has been shown that increased fatigue is associated with an increase in half-relaxation time of torque in the QF of humans with SCI. 30 This suggests that sarcoplasmic reticulum (SR) Ca 2 þ -ATPases are not functioning optimally and/or they are reduced in SCI.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] It has been shown that increased fatigue is associated with an increase in half-relaxation time of torque in the QF of humans with SCI. 30 This suggests that sarcoplasmic reticulum (SR) Ca 2 þ -ATPases are not functioning optimally and/or they are reduced in SCI.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that hypoxemia impairs Ca 2ϩ release and, particularly, Ca 2ϩ uptake by the sarcoplasmic reticulum (10), probably via a decrease in the number of functional Ca 2ϩ release channels (12). The effect of hypoxemia on Ca 2ϩ cycling may occur via several mechanisms, including a more rapid accumulation of hydrogen ions (1), inorganic phosphate (21), and/or free radicals (35).…”
Section: Characteristics and Causes Of Muscle Fatiguementioning
confidence: 99%
“…10 Another common theory of muscle fatigue involves the impaired control of calcium (Ca 2 þ ) release into the sarcoplasmic reticulum. 15 Alterations in the function and concentration of Ca 2 þ ATPase have been suggested after SCI to explain the slowing of relaxation time 12 and changes in sarcoplasmic reticulum Ca 2 þ ATPase isoform expression. 11 The phenomenon of enhanced force after a brief maximal summated contraction is known as post-activation potentiation or post-tetanic potentiation, depending on whether the stimulus is voluntary (post-activation potentiation) or electrically stimulated (post-tetanic potentiation).…”
Section: Discussionmentioning
confidence: 99%